PENGARUH UKURAN, KOMPLEKSITAS, PROGRAM INTERNASIONAL, DAN STATUS AKREDITASI TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL PADA UNIVERSITAS MUHAMMADIYAH DI INDONESIA - Desti Aulia; Ihyaul Ulum; Endang Dwi Wahyuni (Jurnal Akademi Akuntansi, 2019)
The purpose of this study was to identify the effect of size, complexity, international programs, and accreditation status on the disclosure of intellectual capital at Muhammadiyah universities in Indonesia. This study uses purposive sampling with a sample of 41. The IC component used in this study is the Leitner (2002) framework developed by Ulum (2012) which consists of 46 items. Data analysis using content analysis and WarpPLS 6.0. The results showed that the disclosure of Intellectual Capital at each University was different, in terms of the amount of information disclosed, the size of the Muhammadiyah University had a significant positive effect on the disclosure of intellectual capital, as well as the complexity, international programs, and accreditation status had a significant positive effect on the disclosure of the Muhammadiyah University's 4ICU version 2018.